Hubungan Moderasi Beragama Dan Toleransi - Nurhalimah; Uswatun hasanah; Nurwahid (AL-Ikhtiar : Jurnal Studi Islam, 2024)
This research aims to investigate the relationship between religious moderation and tolerance in the context of society. Religious moderation is defined as a moderate attitude in religious practices, while tolerance refers to the ability of individuals or groups to accept differences and appreciate pluralism in society. The results of the analysis show a positive relationship between religious moderation and tolerance. Individuals who have a moderate attitude in religious practices tend to be more tolerant of differences and more accepting of pluralism in society. This research provides an important contribution to understanding the importance of religious moderation in building tolerance and harmony among religious communities. Proposed policy implications include increasing religious education that emphasizes the values of moderation and tolerance, as well as promoting interfaith dialogue to strengthen tolerance and harmony in society. Abstrak Penelitian ini bertujuan untuk menginvestigasi hubungan antara moderasi beragama dan toleransi dalam konteks masyarakat. Moderasi beragama didefinisikan sebagai sikap moderat dalam praktik keagamaan, sementara toleransi merujuk pada kemampuan individu atau kelompok untuk menerima perbedaan dan menghargai pluralitas dalam masyarakat. Hasil analisis menunjukkan adanya hubungan positif antara moderasi beragama dan toleransi. Individu yang memiliki sikap moderat dalam praktik keagamaan cenderung lebih toleran terhadap perbedaan dan lebih menerima pluralitas dalam masyarakat. Penelitian ini memberikan kontribusi penting dalam memahami pentingnya moderasi beragama dalam membangun toleransi dan kerukunan antar umat beragama. Implikasi kebijakan yang diusulkan termasuk peningkatan pendidikan agama yang menekankan nilai-nilai moderasi dan toleransi serta promosi dialog antaragama untuk memperkuat toleransi dan kerukunan di masyarakat.